Judicial Activism Vs Judicial Restraint Batas Legitimasi Hakim dalam Penafsiran Konstitusi di Indonesia - Zul Fadll; Herman; Taufik Firmanto (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The debate on judicial activism and judicial restraint represents a crucial issue in constitutional interpretation practices in Indonesia, particularly regarding the role of judges in balancing constitutional supremacy and democratic principles. This study aims to analyze the limits of judicial legitimacy in constitutional interpretation by examining the tendency toward activism and restraint in constitutional court decisions. This research employs a normative juridical method using statutory and case approaches, focusing on decisions of the Constitutional Court. The findings indicate that judicial activism is necessary in certain circumstances to fill legal gaps and protect constitutional rights, but it risks exceeding legitimate boundaries without strong reasoning and prudential principles. Conversely, judicial restraint helps maintain legal stability but may hinder legal development if applied rigidly. Therefore, a balance between these approaches is essential, grounded in the constitution, the rule of law, and principles of justice. This study concludes that the limits of judicial legitimacy lie in maintaining independence while ensuring accountability in constitutional interpretation.